DAMPAK DIGITALISASI PENDIDIKAN TERHADAP KOMUNIKASI INTERPERSONAL SISWA MADRASAH ALIYAH NEGERI KARO - Mailin Mailin; Muhammad Yasir Halomoan Nasution; Ardiansyah Ardiansyah; Ahmad Nazri Adlani Nst (JGK (Jurnal Guru Kita), 2021)
The purpose of this paper is of course to determine the impact of digitalization of education on interpersonal communication of Karo State Madrasah Aliyah students in the social environment and within the school environment. This research method is qualitative. The results of this study are: The presence of digitalization which is a development of technology has changed the paradigm and pattern of community communication. The existence of this media makes communication not only done in one direction but can be done in two directions. The use of ineffective digitization will have a tremendous impact, one of which users will spend a lot of time just to access various kinds of digitization. But the effective use of digitization will make it easier for students to get information that is really needed so that they can generate creative ideas to support communication development. The most visible impact of digitization for students at MAN Karo is the decline in interpersonal communication activities. This will have an impact on services at MAN Karo. Students are more likely to use or access digitalization than to carry out interpersonal communication. This phenomenon can result in a lack of student awareness so that it will also have an impact on interpersonal relationships. Even though we know that interpersonal communication between students is very important considering that currently technological advances have changed the existence of communication. Therefore, students are expected to be professional in carrying out their duties and functions. One way is to always carry out interpersonal communication in solving any existing problems and maintaining good interpersonal relationships.